Restorative justice as an alternative criminal dispute resolution for the offence of theft - Ab Aziz, Norjihan; Mohamad Amin, Noor Shuhadawati; Ab Hamid, Zuraini (International Organization Center of Academic Research (OCERINT), 2017)
Under the traditional justice system, theft is an offence against a state. Once the offender is found guilty by the court, he will be punished accordingly. In Malaysia, the Penal Code provides punishment for an offence of theft is imprisoned with a term not more than seven years, or fine or imprisonment. The aim is to punish the offender for the offence that he had committed, while the victim has no place in the process. However, restorative justice sees a crime is against an individual which allows the offender to be direct accountability against the victim. In other words, instead of punishing the offender for an offence done, the offender has to repair the harm suffered by the victim such as by paying compensation or in case of theft restore the stolen property to the victim. Islamic law has implemented restorative justice long time ago to allow certain criminal cases to be resolved between the parties, provided that the case has not been reached to the authority. Restorative justice has been recognized internationally by the United Nation, which encourages criminal cases which are minor in nature, such as theft, vandalism, and hurt to be resolved through the restorative justice process. As such, many countries have implemented restorative justice, such as the United Kingdom, the United States, Australia and New Zealand. Restorative justice can be considered as an alternative to the traditional justice system which allows the offender and the victim resolve criminal offence with the assistance of a neutral third party out of court. For instance, in the offence of theft, instead of punishing the offender, the case can be resolved if the offender agrees to seek forgiveness and returns the stolen item or pays compensation to the victim, and the victim agrees to reintegrate the accused into the society. Thus, this research aims to examine the law of Malaysia that governs the offence and the punishment of theft. This research also analyses how restorative justice is implemented under the United Nation and Islamic law. It is suggested that the Malaysian law that governs the offence of theft to be improvised so that the parties may opt to resolve criminal cases through restorative justice.